Perfusion and infusion complications - Stehlin (Jr.), John S. (Congresos Uruguayos de Cirugía, 1965)
Between December, 1957 and October, 1965, 509 perfusions were performed for patients at the M. D. Anderson Hospital. Incluye discusión en pdf adjunto, páginas 75-80